Kualitas Pelayanan Pajak Kendaraan Bermotor Pada Kantor Sistem Administrasi Manunggal Satu Atap Putri Hijau Medan Utara - Fadlan Minallah; Lusiana Andariani Lubis; Nurman Achmad (PERSPEKTIF, 2021)
This research aims to determine and analyze to analyze the quality of service at the Office of the One Roof One-Stop Administration System (SAMSAT) Putri Hijau, Medan Utara. To answer the service quality of Motor Vehicle Tax at the SAMSAT Putri Hijau, the researchers used five dimensions of public service quality proposed by Zeithaml et al in Hardiansyah, namely Tangible, Reliability, Responsiveness. ), Assurance (Guarantee), and Emphaty (Empathy). This study uses a descriptive research method with a qualitative approach. Data collection techniques using interviews, observation, and documentation. Based on the results of the study, it can be concluded that the service quality of the Motor Vehicle Tax (PKB) at the SAMSAT Putri Hijau can be assessed from five dimensions, namely Tangibel, Reliability, Responsiveness, Assurance, and Emphaty, however, there are several indicators. which have not been fulfilled properly, such as regarding the comfort of the place of storage and the existence of discrimination or prioritizing relatives in the motor vehicle tax collection process.